2019
DOI: 10.1371/journal.pone.0215116
|View full text |Cite
|
Sign up to set email alerts
|

Is there more room to improve? The lifespan trajectory of procedural learning and its relationship to the between- and within-group differences in average response times

Abstract: Characterizing the developmental trajectories of cognitive functions such as learning, memory and decision making across the lifespan faces fundamental challenges. Cognitive functions typically encompass several processes that can be differentially affected by age. Methodological issues also arise when comparisons are made across age groups that differ in basic performance measures, such as in average response times (RTs). Here we focus on procedural learning–a fundamental cognitive function that underlies the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
54
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 62 publications
5
54
2
2
Order By: Relevance
“…Moreover, Gao et al 57 in a recent study showed that www.nature.com/scientificreports www.nature.com/scientificreports/ above-average cognitive abilities buffer against insufficient sleep durations. However, not all cognitive functions peak in adulthood: while previous studies have reported the best performance in working memory and executive functions in young adulthood [58][59][60][61] , some aspects of procedural learning (as measured by the ASRT task) has been shown to peak in childhood and to decline already around adolescents 44,62,63 . Consequently, a cognitive peak may explain finding no relationship between subjective sleep quality and aspects of working memory and executive functions, while this explanation for the measures of procedural learning seems unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Gao et al 57 in a recent study showed that www.nature.com/scientificreports www.nature.com/scientificreports/ above-average cognitive abilities buffer against insufficient sleep durations. However, not all cognitive functions peak in adulthood: while previous studies have reported the best performance in working memory and executive functions in young adulthood [58][59][60][61] , some aspects of procedural learning (as measured by the ASRT task) has been shown to peak in childhood and to decline already around adolescents 44,62,63 . Consequently, a cognitive peak may explain finding no relationship between subjective sleep quality and aspects of working memory and executive functions, while this explanation for the measures of procedural learning seems unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…However, older adults benefit less from intervening sleep than younger ones, which indicates that the consolidation process in particular seems to be affected by ageing (Howard & Howard, 2013;Nemeth & Janacsek, 2011). Other studies found that older adults performed as well or even better than young adults (e.g., Juhasz et al, 2019). For instance, Verneau and colleagues (2014) found that older adults performed as well as younger adults on the ASRT when no explicit information about underlying rules was given; and in contrast to the younger group, their performance did LANGUAGE LEARNING AND AGEING 4 not benefit from such information.…”
mentioning
confidence: 97%
“…Such learning underlies the acquisition of, for instance, motor and language skills. It is often assumed that implicit learning skills -in contrast to other cognitive abilities such as working memory, attention, and cognitive control (e.g., Hedden & Gabrieli, 2004;Craik & Bialystok, 2006) -are relatively preserved in ageing (e.g., Verneau, van der Kamp, Savelsbergh, & de Looze, 2014; see Howard & Howard, 2013, for a review) and may serve as a shield against age-related cognitive decline (Palmer, Hutson & Mattys, 2018;Juhasz, Nemeth & Janacsek, 2019). The current study aims to investigate whether preserved learning across age also extends to more complex skills that involve learning arbitrary dependencies implicitly, such as language.…”
mentioning
confidence: 99%
“…This is in line with previous behavioral (cf. Juhasz et al, 2019; Szegedi-Hallgató et al, 2019; Török, Janacsek, Nagy, Orbán, & Nemeth, 2017) and ERP results (Kóbor, Horváth, Kardos, Takács, et al, 2019; Kóbor et al, 2018), proposing that the sensitivity to multiple probabilistic regularities has possibly been grounded in the implicit extraction of the triplet-level probability structure.…”
Section: Discussionmentioning
confidence: 99%
“…Independent of triplet types, general skill improvements (faster RTs) reflecting more efficient visuomotor and motor-motor coordination due to practice were also considered (cf. Hallgató, Győri-Dani, Pekár, Janacsek, & Nemeth, 2013; Juhasz, Nemeth, & Janacsek, 2019).…”
Section: Methodsmentioning
confidence: 99%